Application of Intelligent Systems in Multi-modal Information Analytics : Proceedings of the 2020 International Conference on Multi-model Information Analytics (MMIA2020), Volume 1 /: Proceedings of the 2020 International Conference on Multi-model Information Analytics (MMIA2020), Volume 1. (2020) - Unknown
No abstract available